PELATIHAN DAN PENDAMPINGAN KADER KESEHATAN GIGI PADA GURU SD MELALUI PROGRAM SQUID SMILE (SAVE QUALITY OF INDONESIAN CHILDREN SMILE): TRAINING AND MENTORING OF DENTAL HEALTH CADRES FOR ELEMENTARY SCHOOL TEACHERS THROUGH THE SQUID SMILE PROGRAM (SAVE QUALITY OF INDONESIAN CHILDREN SMILE) - Hollanda, Ghita; Pinasti RA; Maharani AD; Mustami'ah, Dewi (Universitas Hang Tuah Surabaya, 2025)
High rates of dental caries and low oral hygiene status are oral health problems that are often found in children's age groups. Based on Riskesdas data in 2018, it was reported that the prevalence of dental and oral problems in Indonesia was 57.6% and only 10.2% received dental medical treatment. An optimal level of public dental health can be achieved if each individual and community group has the knowledge, awareness, ability, and willingness to maintain good dental health. The training program for elementary school teachers can be an alternative to optimize the improvement of the dental and oral health status of students at the elementary school level, namely the “Squid Smile” training program and synergize with the School Dental Health Effort program. This training activity is carried out in several stages as follows: a) Training and education related to the psychological development of elementary school-age children; b) Training and education related to dental and oral health of elementary school-age children; c) Preparation of the School Dental Health Efforts (UKGS) Program; d) Monitoring and Evaluation of the implementation of the School Dental Health Efforts (UKGS) program. The results of this training had a positive impact on the participants or teachers who participated. The increase in knowledge possessed by teachers or participants is an initial provision for the implementation of UKGS at SD Muhammadiyah 9 Surabaya. In addition, there is also a need for training and professional development for teachers to improve their understanding of children's cognitive development. With better knowledge, teachers can design learning experiences that are more effective and support students' cognitive development